Enhancing software development through project‐based learning and the quality of planning. (4th September 2020) - Amaral Féris, Marco Antônio; Goffin, Keith; Zwikael, Ofer; Fan, Di
Abstract : R&D plays a crucial role in developing new products, the commercialisation of which can drive corporate growth. Over three decades, research has focused the new product development (NPD) process and it is known that developing new products is a knowledge‐intensive, risky activity. Since industry surveys show that many NPD projects, particularly software‐based ones, fail to meet their schedules and objectives. Consequently, today's R&D managers still need ways to plan and conduct NPD more effectively. Project‐based Learning (PBL) – the generation of specific technical and process knowledge during and after a project – is a potential way to improve NPD. Therefore, this paper investigated the research question: Does PBL enhance the quality of planning in subsequent software development projects? The study used a sample of 47 software development projects at three multinational organisations. Significantly, the findings show that PBL does enhance the quality of planning of subsequent software development projects. In particular, the quality of planning is increased in projects with high levels of uncertainty; where team members work in a project‐based structure with strong collaboration; and when the pressure to deliver projects is high. The contribution of the research at a theoretical level is that it identified an important link between learning and the quality of planning in subsequent NPD projects. At a practical level, the study identifies specific steps R&D managers can take to improve the performance of software development projects, with all their associated challenges.